2020
DOI: 10.3390/a13040097
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment of Predictive Control—A Survey

Abstract: Model Predictive Control constitutes an important element of any modern control system. There is growing interest in this technology. More and more advanced predictive structures have been implemented. The first applications were in chemical engineering, and now Model Predictive Control can be found in almost all kinds of applications, from the process industry to embedded control systems or for autonomous objects. Currently, each implementation of a control system requires strict financial justification. Appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…However, the linearization is created based on the approximated procedure and it does not take into account the full dynamics of the real system. Among these control techniques, the model predictive control (MPC) provided good performance for a lot of engineering applications [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the linearization is created based on the approximated procedure and it does not take into account the full dynamics of the real system. Among these control techniques, the model predictive control (MPC) provided good performance for a lot of engineering applications [14].…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that the outlier robustness aspect is not as such addressed. On the other hand, robust indexes are successfully used in the MPC control performance assessment [31]- [33], which is independent of the controller operation, however, should reflect predictive operation.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the discussed tuning approach makes it possible to use very good control quality, much better than in the most common case in which all tuning parameters are constant. The multicriteria control assessment is used since the control quality is assessed taking into account three factors: the sum of squared errors, the Huber standard deviation and the entropy [36,37].…”
Section: Introductionmentioning
confidence: 99%